Influenza B virus: need for heightened surveillance and epidemiologic case studies - Rayamajhi, Nabin; Joshi, Arabind; Pangeni, Raju Prasad; Upadhyaya, Bishnu; Shakya, Geeta; Shah, Jay N; Karki, Arjun; Baral, Kedar P (Journal of Patan Academy of Health Sciences, 2015)
Recent report of increased influenza B virus infection, particularly the clinical profiles and treatment challenges imposed like that of influenza A, underscores the importance of continuing influenza B virus surveillance. This is, especially in resource limited country, early detection of influenza virus, its clinical presentation and complications would be vital in minimizing the public heath burden imposed by this virus. Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):52-54